Immigration(s) et accès aux soins en Guyane - Estelle Carde (Anthropologie & Santé)
Immigration in French Guyana is plural. Caribbean migrants, driven away by poverty and political violence, mix with migrants who left metropolitan France to taste the exotism of this French society in South America. This plurality shapes access to health care, since foreign users meet French professionals who are either native or migrants. These foreigners may be victims of discrimination on the part of native professionals who suspect them of taking advantage of the local health care system. Whereas such discrimination exists elsewhere in France, the situation seems exacerbated in French Guyana by the importance of the migratory flows and socioeconomic difficulties. Migrant professionals represent another figure in the access to health care in a context of immigration, more specific to French Guyana. They sometimes attribute a native status to some of their foreign users which is not recognized by the law. Finally, these stakes of access to health care in the context of immigration are linked to a set of unequal social relations that cross Guyanese society.